2014
DOI: 10.1111/ajt.12841
|View full text |Cite
|
Sign up to set email alerts
|

First Confirmed Cases of Middle East Respiratory Syndrome Coronavirus (MERS-CoV) Infection in the United States, Updated Information on the Epidemiology of MERS-CoV Infection, and Guidance for the Public, Clinicians, and Public Health Authorities—May 2014

Abstract: This report highlights the first two cases of MERS coronavirus in the United States. Although these patients were not transplant recipients, it is important for transplant professionals to be aware of this infection and to consider it when evaluating patients with respiratory illnesses and travel to the Arabian peninsula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Our results suggest that the "border policy issue" has continuously been a concern for Canadians, who support strict border measures to prevent the spread of COVID-19 in Canada. Previous studies demonstrated that air transportation has the potential to spread influenza, such as A/H1N1 [22], and enhanced precautions should be taken for travelers to countries with increasing cases of respiratory diseases, such as Middle East respiratory syndrome [23]. Brown and colleagues [24] showed that airport exit and entry screening at international borders facilitated the rapid detection of illness and the implementation of appropriate public health control measures to prevent the spread of Ebola virus.…”
Section: Theme 1: Strict Border Measuresmentioning
confidence: 99%
“…Our results suggest that the "border policy issue" has continuously been a concern for Canadians, who support strict border measures to prevent the spread of COVID-19 in Canada. Previous studies demonstrated that air transportation has the potential to spread influenza, such as A/H1N1 [22], and enhanced precautions should be taken for travelers to countries with increasing cases of respiratory diseases, such as Middle East respiratory syndrome [23]. Brown and colleagues [24] showed that airport exit and entry screening at international borders facilitated the rapid detection of illness and the implementation of appropriate public health control measures to prevent the spread of Ebola virus.…”
Section: Theme 1: Strict Border Measuresmentioning
confidence: 99%
“…During new and emerging public health threats to the nation, rapid development of data collection processes and tools is required to collect critical data for response decisions. Historically, the collection of critical data has been demonstrated during recent public health threats such as anthrax in 2001 1 and 2015, 2 severe acute respiratory syndrome (SARS) in 2003, 3 Marburg hemorrhagic fever in 2008, 4 influenza A subtype H1N1 in 2009, 5 , 6 Middle East respiratory syndrome coronavirus (MERS-CoV) in 2012 7 and 2014, 8 Ebola hemorrhagic fever in 2014 9 and 2019, 10 the Flint water crisis in Michigan in 2016, 11 and Zika in 2016. 12 Following the report of a novel coronavirus infection in Wuhan City, Hubei Province, China, CDC engaged the international public health community to identify this global threat, now known to be caused by the SARS-CoV-2 virus.…”
mentioning
confidence: 99%